2009
DOI: 10.1093/europace/eup121
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of atrioventricular nodal re-entrant tachycardia by cryoablation with a 6 mm-tip catheter vs. radiofrequency ablation

Abstract: Compared with RF ablation, CRYO with 6 mm-tip catheter for treating AVNRT results in higher recurrence and potentially lower incidence of permanent AVB. Fluoroscopy time has been shown to be reduced by CRYO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…Several retrospective series 8,12,16,17 did not find a significant difference in procedure duration between cryoablation and RF, and only Chan et al 16 reported a significantly shorter fluoroscopy time in the cryoablation group (18 versus 26 minutes). In our experience, the longer procedure duration is not so much due to the time needed to install the cryoablation console and start the system but more to the time needed to perform multiple cryoablation mappings (each of 3 minutes' duration) with a large number of sites sometimes tested before ablating.…”
Section: Procedures and Fluoroscopy Timementioning
confidence: 97%
See 2 more Smart Citations
“…Several retrospective series 8,12,16,17 did not find a significant difference in procedure duration between cryoablation and RF, and only Chan et al 16 reported a significantly shorter fluoroscopy time in the cryoablation group (18 versus 26 minutes). In our experience, the longer procedure duration is not so much due to the time needed to install the cryoablation console and start the system but more to the time needed to perform multiple cryoablation mappings (each of 3 minutes' duration) with a large number of sites sometimes tested before ablating.…”
Section: Procedures and Fluoroscopy Timementioning
confidence: 97%
“…4,7,8,10 -13,15 Several authors report that using a 4-mm-tip ablation catheter achieved only moderate success rates, 11,12 whereas in more recent series with 6-mm-tip cryoablation catheters, short-term success rates of 93% to 99% were reached. 13,16,17 We used a 6-mm-tip catheter, an ablation time of 4 minutes, and a bonus freeze at the site of successful ablation. With this practice, a high short-term success rate (96.8%) comparable to RFCA (98.4%) was found.…”
Section: Short-term Successmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review that combined 22 published studies (including 2654 patients), cryothermal ablation had a high procedural success rate (95%; range, 85%-99%) that was comparable with RFCA (95%-98%). [30][31][32][35][36][37][38][39][40][41][42][43][44][45][46][47] Long-term freedom from recurrent arrhythmia with cryoablation was reported to be 89% (range, 81.3%-98%), which was lower than historical observations with RF (3%-7% recurrence). 32 Although historical comparisons between observational studies are fraught with potential biases, 11 comparative studies between cryothermy and RFCA for AVNRT (8 retrospective observational studies and 3 prospective randomized studies; Table 1), reported comparable acute success rates.…”
Section: Av Nodal Reentrant Tachycardiamentioning
confidence: 99%
“…32 Although historical comparisons between observational studies are fraught with potential biases, 11 comparative studies between cryothermy and RFCA for AVNRT (8 retrospective observational studies and 3 prospective randomized studies; Table 1), reported comparable acute success rates. [36][37][38][39][40][41][42][43][44][45][46][47] Although the longer term recurrence rate was statistically similar in 7 of the 11 studies, there was an overall trend that favored RFCA. Procedural duration was globally similar, with a shorter fluoroscopy time with cryoablation.…”
Section: Av Nodal Reentrant Tachycardiamentioning
confidence: 99%